Heron's Formula

Hi, can you help me prove Heron's Formula? Just put your proof down below this comment.

#Algebra #Heron'sFormula

Note by Jonathan Hsu
5 years, 11 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

The perimeter of the\large{\text{The perimeter of the}} ΔABC\Delta ABC is given by P=a+b+c\large{\text{is given by P=a+b+c}}

Area of\large{\text{Area of}} ΔABC=12bh.........................1\large{\Delta ABC = \dfrac{1}{2}bh}.........................\boxed{1}

From\large{\text{From}} ΔADB, \large{\Delta ADB} ,

x2+h2=c2\large{x^2 + h^2 = c^2} [Using Pythagoras theorem]

x2=c2h2\large{x^2 = c^2 - h^2}

x=c2h2\large{x = \sqrt{c^2 - h^2}}.

From\large{\text{From}} ΔCDB \large{\Delta CDB}

(bx)2+h2=a2\large{(b - x)^2 + h^2 = a^2} [Using Pythagoras theorem]

(bx)2=a2h2\large{(b - x)^2 = a^2 - h^2}

b22bx+x2=a2h2\large{b^2 - 2bx + x^2 = a^2 - h^2 }

Substitute the values of \large{\text{Substitute the values of }} x\large{x} and\large{\text{and}} x2\large{x^2}

b22bc2h2+(c2h2)=a2h2\large{b^2 - 2b\sqrt{c^2 - h^2} + (c^2 - h^2) = a^2 - h^2}

b2+c2a2=2bc2h2\large{b^2 + c^2 - a^2 = 2b\sqrt{c^2 - h^2}}

Squaring on both sides,\large{\text{Squaring on both sides,}}

(b2+c2a2)2=4b2(c2h2)\large{(b^2 + c^2 - a^2)^2 = 4b^2(c^2-h^2)}

(b2+c2a2)24b2=(c2h2)\large{\dfrac{(b^2+c^2-a^2)^2}{4b^2} = (c^2-h^2)}

h2=c2(b2+c2a2)24b2\large{h^2=c^2 -\dfrac{(b^2+c^2-a^2)^2}{4b^2}}

h2=4b2c2(b2+c2a2)22b2\large{h^2 = \dfrac{4b^2c^2 -(b^2+c^2-a^2)^2}{2b^2} }

h2=(2bc)2(b2+c2a2)4b2\large{h^2 = \dfrac{(2bc)^2 - (b^2+c^2-a^2)}{4b^2}}

h2=[2bc+(b2+c2a2)][2bc(b2+c2a2)]4b2\large{h^2 = \dfrac{[2bc +(b^2+c^2-a^2)][2bc -(b^2+c^2-a^2)]}{4b^2}}

h2=[2bc+b2+c2a2][2bcb2c2+a2]4b2\large{h^2=\dfrac{[2bc+b^2+c^2-a^2][2bc -b^2-c^2+a^2]}{4b^2}}

h2=[(b2+c2+2bc)a2][2bc(b2+c22bc)]4b2\large{h^2=\dfrac{[(b^2+c^2+2bc)-a^2][2bc-(b^2+c^2-2bc)]}{4b^2}}

h2=[(b+c)2a2][a2(bc)2]4b2\large{h^2 = \dfrac{[ \, (b + c)^2 - a^2 \, ] [ \, a^2 - (b - c)^2 \, ]}{4b^2}}

h2=[(b+c)+a][(b+c)a][a+(bc)][a(bc)]4b2\large{h^2 = \dfrac{[ \, (b + c) + a \, ][ \, (b + c) - a \, ] [ \, a + (b - c) \, ][ \, a - (b - c) \, ]}{4b^2}}

h2=(b+c+a)(b+ca)(a+bc)(ab+c)4b2\large{h^2 = \dfrac{(b + c + a)(b + c - a)(a + b - c)(a - b + c)}{4b^2}}

h2=(a+b+c)(b+ca)(a+cb)(a+bc)4b2\large{h^2 = \dfrac{(a + b + c)(b + c - a)(a + c - b)(a + b - c)}{4b^2}}

h2=(a+b+c)(a+b+c2a)(a+b+c2b)(a+b+c2c)4b2\large{h^2 = \dfrac{(a + b + c)(a + b + c - 2a)(a + b + c - 2b)(a + b + c - 2c)}{4b^2}}

h2=P(P2a)(P2b)(P2c)4b2\large{h^2 = \dfrac{P(P - 2a)(P - 2b)(P - 2c)}{4b^2}}

h=P(P2a)(P2b)(P2c)2b\large{h = \dfrac{\sqrt{P(P - 2a)(P - 2b)(P - 2c)}}{2b}}

Substitute h to\large{\text{Substitute h to}} 1\boxed{1}

A=12bP(P2a)(P2b)(P2c)2b\large{A = \dfrac{1}{2}b\dfrac{\sqrt{P(P - 2a)(P - 2b)(P - 2c)}}{2b}}

A=14P(P2a)(P2b)(P2c)\large{A = \dfrac{1}{4}\sqrt{P(P - 2a)(P - 2b)(P - 2c)}}

A=116P(P2a)(P2b)(P2c)\large{A = \sqrt{\dfrac{1}{16}P(P - 2a)(P - 2b)(P - 2c)}}

A=P2(P2a2)(P2b2)(P2c2)\large{A = \sqrt{\dfrac{P}{2} \left( \dfrac{P - 2a}{2} \right)\left( \dfrac{P - 2b}{2} \right)\left( \dfrac{P - 2c}{2} \right)}}

A=P2(P2a)(P2b)(P2c)\large{A = \sqrt{\dfrac{P}{2} \left( \dfrac{P}{2} - a \right)\left( \dfrac{P}{2} - b \right)\left( \dfrac{P}{2} - c \right)}}

We know that s =\large{\text{We know that s =}}P2\large{\dfrac{P}{2}}

A=s(sa)(sb)(sc)\Large{\boxed{\therefore A=\sqrt{s(s-a)(s-b)(s-c)}}}

Sai Ram - 5 years, 5 months ago

This is the diagram :

file:///C:/Users/Abhi/Desktop/Capture.JPG

Sai Ram - 5 years, 5 months ago
×

Problem Loading...

Note Loading...

Set Loading...